Performance Analysis of the Electric Tracked Vehicle Coupling Transmission Scheme - Jia Xiaoping; Ma Jun; Yu Kuilong; Li Jiong (Jixie chuandong)
For the motor performance demanding disadvantage in tracked vehicle bilateral independent motor drive scheme,a power coupling scheme is proposed. By analyzing the performance characteristic and speed,torque mathematical transformation model of the coupling mechanism,the feasibility of coupling scheme is demonstrated. Explains most of the power coupling mechanism can turn the power back through mechanical means by dynamics calculation,and the power requirements of the tracked vehicle steering can be significantly reduced. The analysis results verify the correctness and feasibility of the scheme,and a new idea for the electric drive tracked vehicle scheme selection is provided.